Perencanaan Gearboxdan Perhitungan Daya Motor pada Modifikasi Dongkrak Ulir Mekanis Menjadi Dongkrak Ulir Elektrik - Ahmad Suudi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2013)
Manual jackscrew is a lifting device used by automobile drivers when any disorders occur, especially when the automobile tires are deflated. Considering manual jackscrew shape and design, not all people are able to use it easily, especially women. This is the reason of manual jackscrew modification into electric jackscrew.This jackscrew modification is conducted by adding a gearbox and DC motor. The ratio between gearbox input and output is 1 : 44.77 and the DC motor power is 160 Watt – 600 Watt. The electric jackscrew working principle is that rotation from DC motor is reduced by the gearbox and forwarded to screw shaft in the jackscrew. The power source is from the automobile battery. The results of electric jackscrew testing show that time of jacking is 10 seconds for tricycle motorbike, 12 seconds for Gran Max PU car, and 14 seconds for Mazda Vantrend car,all the data is compared with the data manual jackscrew.Key words: jack, screw, manual, gearbox, DC motor, and electric